Cloning, localization and expression analysis of vacuolar sugar transporters in the CAM plant Ananas comosus (pineapple). - Antony, E; Taybi, T; Courbot, M; Mugford, S; Smith, J; Borland, A (2008)
In photosynthetic tissues of the CAM plant pineapple (Ananas comosus), storage of soluble sugars in the central vacuole during the daytime and their remobilization at night is required to provide carbon skeletons for nocturnal CO(2) fixation. However, soluble sugars produced photosynthetically must also be exported to support growth processes in heterotrophic tissues. To begin to address how vacuolar sugar storage and assimilate partitioning are regulated in A. comosus, degenerate PCR and cDNA library screening were used to clone three candidate sugar transporters from the leaves of this species. Subcellular localization of the three transporters was investigated via expression of YFP-fusion proteins in tobacco epidermal cells and their co-localization with subcellular markers by confocal microscopy. Using this strategy, a putative hexose transporter (AcMST1) and a putative inositol transporter (AcINT1) were identified that both localized to the tonoplast, whereas a putative sucrose transporter (AcSUT1) was found to localize to prevacuolar compartments. A cDNA (AcMST2) with high similarity to a recently characterized tonoplast hexose transporter in Arabidopsis was also identified from an A. comosus fruit EST database. Analyses of transcript abundance indicated that AcMST1 was more highly expressed in fruits compared to leaves of A. comosus, whilst transcripts of AcINT1, AcSUT1, and AcMST2 were more abundant in leaves. Transcript abundance of AcINT1, the putative inositol transporter, showed day-night changes comparable to those of other CAM-related transcripts described in Mesembryanthemum crystallinum. The results are discussed in terms of the role of vacuolar sugar transporters in regulating carbon flow during the diel cycle in CAM plants.